EFFICIENCY IN RESOURCE USE AND RETURN FROM CROPS CULTIVATION (WITH SPECIAL REFERENCE TO KANNIYAKUMARI) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the efficiency in resource utilization and return from crop cultivation, focusing on Kanniyakumari. Through empirical analysis and case studies, it examines the strategies employed by farmers in the region to maximize resource efficiency while ensuring optimal yields. By exploring various agricultural practices and their impacts on productivity and sustainability, this research aims to provide insights into improving crop cultivation practices in Kanniyakumari and similar agroecological contexts.